Effect of avocado/soybean unsaponifiables on osseointegration: A proof-of-principle preclinical in vivo study - de Oliveira, Guilherme José Pimentel Lopes [UNESP]; de Paula, Luiz Guilherme Freitas [UNESP]; Spin-Neto, Rubens; Stavropoulos, Andreas; Spolidório, Luis Carlos [UNESP]; Marcantonio, Elcio [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP] (Quintessence Publishing, 2014)
Purpose: To evaluate the influence of administration of avocado/soybean unsaponifiables (ASU) on implant osseointegration in rat tibiae. Materials and Methods: Thirty rats were randomly assigned into one of three equal-sized groups: (1) ASU1: administration of ASU starting 7 days prior to implant placement; (2) ASU2: administration of ASU starting on the day of implant placement, and (3) CTL: administration of saline solution. In all animals, one titanium implant was placed in each tibia. All animals received ASU or saline solution by gavage daily until sacrifice 60 days postoperatively. Implant osseointegration and bone maturation were assessed by biomechanical and radiographic bone density analysis; descriptive histology; immunohistochemistry for bone morphogenetic protein 2 (BMP-2), transforming growth factor beta 1 (TGF-β1), and osteocalcin; and histomorphometric evaluation of bone-to-implant contact (BIC) and mineralized bone area fraction within the threads of the implant. Results: ASU1 and ASU2 showed three times higher expression of BMP-2 and nine times higher expression of TGF-β1 compared with CTL (P < .05). Histomorphometric analysis, however, showed that both ASU1 and ASU2 groups presented significantly higher BIC values only in the cortical bone compartment when compared to CTL (P < .05). Conclusion: ASU consumption seems to exert only a subtle effect on implant osseointegration.
Keywords: Animal study; Avocado/soybean unsaponifiables; Histomorphometry; Implant osseointegration